Constraints that registered nurses in Namibia are faced with when utilising the nursing process in local-level Primary health care practice - Iita, Hermine; Iipinge, Scholastika; Van Dyk, Agnes (International Journal of Health, 2016)
The purpose of this study was twofold. Firstly to explore and describe the utilization of the Nursing Process by registered nurses in local level Primary health care practice in Namibia with regard to Primary health care delivery during their daily practices and secondly, to develop strategies that would support registered nurses in executing their role and function in this regard. These were prompted by the implementation of a Primary health care approach to health care delivery in the country. The objectives of the study were:To Explore and describe the way in which registered nurses in clinics, health care centres and outreach posts in the health districts use the nursing process as regards PHC delivery;Â To determine how supervisors perceive the utilisation of the nursing process by registered nurses with regard to PHC;To identify the constraints that registered nurses are faced with when utilising the nursing process with regard to the delivery of PHC;To develop a conceptual framework on which to base the formulation of relevant strategies,To incorporate the findings of this study into the development of strategies to support registered nurses in their utilisation of the nursing process with regard to the delivery of PHC;To validate the appropriateness of these strategies.A multi- phase, quantitative, exploratory, descriptive and contextual design was selected to provide a picture of how registered nurses fulfill their role and function concerning Primary health care (PHC) during their daily practices.The population consisted of two groups. The first group consisted of 239 registered nurses working in Clinics, health Centres and in Outreach Programmes. The second group consisted of 39 registered nurses supervisors, who supervised the registered nurses in these facilities. A survey was used to gather the data through self-report (questionnaire). Two questionnaires were developed, one for registered nurses and the other for immediate supervisors. Quantitative, descriptive analysis was used to summarize and organize data using tables and figures as well as t-test and analysis of variance (ANOVA), where applicable. Five main areas where registered nurses needed support in execution of their roles and functions were revealed from the results. The areas were: Water and sanitation and other environmental health issues; health education and communication including outreach activities; Nutrition and food supply; Community diagnosis and care and Management support or administrative functions in Primary health Care, including research and education of health workers including fellow registered nurses.This paper discusses the constraints that registered nurses in Namibia face when they use the nursing process in local Primary health care facilities.